Method for improving oxidation stability of vegetable oil body by combining tannic acid interface self-assembly
Through the self-assembly technology of the interface components of tannin acid and vegetable oil body, the problem of oxidative instability of vegetable oil body is solved, and its oxidative stability and application value are significantly improved.
Patent Information
- Application Number
- CN202411703977.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
Natural vegetable oils have oxidative instability problems, which affects their application in food, cosmetics, pharmaceuticals and other industries.
Using the interface phospholipids and oleoprotein between tannin and vegetable oil body, self-assembled through hydrogen bonding and hydrophobic interactions, reduce the size of the droplets, enhance the electrostatic repulsion and steric hindrance between the droplets, thereby inhibiting the core lipids and proteins. Oxidation.
It significantly improves the oxidation stability of vegetable oils, inhibits core lipid oxidation by more than 20%, and inhibits protein oxidation by more than 12%, extends the storage stability and nutritional value of the product.
Smart Images

Figure CN119488123A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food, medicine and cosmetics manufacturing, and particularly relates to a method for improving the oxidation stability of plant oil bodies by self-assembly bonding of tannic acid interfaces. Background Art
[0002] Based on colloid science, plant oil bodies are natural micro-nano emulsion droplets composed of phospholipid-oleosin membranes encapsulating core lipids. Due to their unique water-in-oil structure and rich functional ingredients such as polyunsaturated fatty acids, tocopherols, and phytosterols, they have broad application prospects in the food, cosmetics, and pharmaceutical industries, such as functional factor delivery, emulsion gels, edible membranes, targeted delivery of recombinant oil bodies, fat globule membrane replacement, and bioreactors. Therefore, the development of plant oil bodies as a natural resource is a new way to accelerate the realization of green manufacturing strategic needs. However, the oxidative instability of natural plant oil bodies is a difficult problem that needs to be solved in its development. Improving the oxidative stability of plant oil bodies has theoretical value and guiding significance for the production and development of related products.
[0003] At present, most technologies improve the oxidative stability of oils in traditional water-in-oil emulsions by adding antioxidants, especially some naturally derived antioxidants such as plant polyphenols. National patent CN112106975A prepares chitosan and tannic acid composite colloidal particle emulsifiers based on acidic conditions (pH 2-4). The emulsion stabilized by this emulsifier has smaller particle size, stronger stability and antioxidant properties. National patent CN118633675A adjusts the pH of plant protein or animal protein solution to alkaline to dissociate and denature the protein, introduces polyphenols at different stages of pH treatment-mediated protein dissociation and recombination, introduces fat-soluble polyphenols during pH treatment dissociation, and introduces water-soluble polyphenols after protein recombination. Both methods can improve the functional properties of protein particles and prepare emulsions with excellent antioxidant properties. National patent CN118085330A adds polyphenols to a protein solution, covalently binds polyphenols and proteins under alkaline conditions, and the binding product is adsorbed on the surface of the emulsion gel lipid droplets as an emulsifier. After adding a cross-linking agent, the three are filled in the continuous phase to form a three-dimensional network structure. The prepared Pickering emulsion gel has high strength, good emulsification and stability, and is resistant to oil oxidation, which is suitable for 3D printing. National patent CN118235801A uses epigallocatechin gallate to covalently bind zein under alkaline conditions, and adds Ca 2+ The structural strength of the interface coating is enhanced to construct an oil gel with good strength and deformation resistance and not easily oxidized. In summary, the existing patented technologies all promote the interaction between protein and polyphenols under acidic or alkaline conditions. Although the interaction between polyphenols and proteins may be stronger at this time, the digestibility and bioavailability of denatured proteins will be affected.
[0004] Plant oil bodies have a natural oil-water interface structure composed of phospholipids and oil body proteins (the most important interface proteins) self-assembled into an outer membrane. At present, there is no related technology for designing the plant oil body interface based on the interaction between polyphenols and oil body interface components (phospholipids, oil body proteins) to improve its oxidative stability. Generally speaking, lipid oxidation in emulsions is always accompanied by protein oxidation. Protein antioxidant amino acids (such as cysteine) exposed on the surface of plant oil bodies can be used as metal chelators and free radical scavengers as sacrificial reductants to prevent central lipid oxidation. However, on the contrary, lipid oxidation products, such as free radicals, hydroperoxides and carbonyl compounds, can promote protein oxidation. However, related research techniques only focus on the ability of polyphenols to prevent lipid or protein oxidation in single-component model systems, and the effects of natural antioxidants on the co-oxidation of lipids and proteins in plant oil body emulsion systems have not been fully explored. Summary of the invention
[0005] The present invention proposes to utilize tannic acid (C 76 H 52 O 46 ) This hydroxyl-rich, high molecular weight, amphiphilic natural polyphenol self-assembles with phospholipids and oil body proteins at the plant oil body interface under neutral conditions through hydrogen bonds and hydrophobic interactions, reducing the size of plant oil body droplets, reducing the exposure of positively charged groups on the oil body surface, inducing strong electrostatic repulsion and long droplet spacing, thereby avoiding aggregation and coalescence caused by mutual attraction between droplets. The natural water-in-oil structure interface layer of the oil body is more compact, limiting the diffusion of pro-oxidants, inhibiting the oxidation of core lipids and proteins, and thus improving the oxidative stability of natural plant oil bodies. The present invention is of great significance for improving the storage stability, nutritional value and sensory quality of oil body products.
[0006] The present invention uses tannic acid and the interfacial phospholipids and oil body proteins of plant oil bodies to self-assemble through hydrogen bonds and hydrophobic interactions under neutral and mild conditions, with the aim of inhibiting the oxidation of core lipids and proteins in oil bodies and improving the oxidative stability of natural plant oil bodies, thereby providing a technical basis for designing and applying a stable plant oil body-based system.
[0007] The objective of the present invention is achieved through the following technical solutions: A method for improving the oxidative stability of plant oil bodies by interfacial self-assembly of tannic acid, comprising the following steps: (1) Preparation of natural plant oil bodies Mix crushed soybeans, peanuts, flax seeds, almonds, walnuts or rice bran with NaHCO3 solution in proportion, incubate for a certain period of time, filter the slurry, centrifuge the filtrate, collect the cream layer, wash with water and centrifuge again to obtain plant oil bodies.
[0008] (2) Construction of plant oil emulsions with tannic acid interfacial self-assembly Tannic acid powder was dispersed in phosphate buffer (0.01 M, pH 7.0) at a concentration of 0.2-1 mg / mL. Tannic acid solutions of different concentrations were mixed with plant oil bodies (1:0.2-1, w / w), the pH of the mixture was adjusted to 7.0, and the mixture was stirred in a closed chamber at 25 °C for 1-2 h, and then dialyzed (molecular weight cutoff 3.5 kDa) at 4 °C for 24 h (deionized water was replaced 10 times) to remove unreacted tannic acid, and finally a plant oil body emulsion with tannic acid interfacial self-assembly was obtained.
[0009] The beneficial effects of the present invention are: Compared with the existing invention technology that uses extreme conditions to modify proteins in traditional emulsions to improve emulsion stability, the present invention uses tannic acid, a hydroxyl-rich, high-molecular-weight natural polyphenol, to self-assemble with the interfacial phospholipids and oil body proteins of plant oil bodies through hydrogen bonds and hydrophobic interactions under mild conditions. First, the plant oil bodies can still maintain the natural water-in-oil structure of the core lipids coated by the phospholipid-oil body protein membrane, but the droplet size is reduced, the electrostatic repulsion and steric hindrance between the droplets are enhanced, the interface layer is denser, and the diffusion of pro-oxidants is limited. Therefore, the oxidation of core lipids and proteins in the plant oil bodies can be effectively inhibited, thereby promoting the industrial application of natural plant oil bodies in food, medicine, and cosmetic systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The laser confocal microscope and transmission electron microscope images of comparative example 2 (A1, A2), example 1 (B1, B2), and example 2 (C1, C2) are shown. In the laser confocal microscope images (A1, B1, C1), the oil droplets are green and the protein is red; Figure 2 These are photos of the appearance of Comparative Example 1, Example 1, and Example 2 during storage; Figure 3 It is a graph of lipid hydroperoxide concentration of Comparative Example 1, Example 1, and Example 2 during storage; Figure 4 The graphs are for protein carbonyl content of Comparative Example 1, Example 1, and Example 2 during storage; Figure 5 It is a graph of free thiol content of Comparative Example 1, Example 1, and Example 2 during storage; Figure 6 The Raman spectra of Comparative Example 1, Example 1 and Example 2 are shown; Figure 7 It is the infrared spectra of comparative example 1, embodiment 1 and embodiment 2; Figure 8 The secondary structure composition of the oil body protein of Comparative Example 1, Example 1 and Example 2; Fig. 9It is a structural simulation diagram of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, and Example 2. DETAILED DESCRIPTION
[0011] The present invention provides a method for improving the oxidative stability of plant oil bodies by interfacial self-assembly of tannic acid. In order to make the purpose, technical scheme and effect of the present invention clearer, the present invention will be further described in detail with reference to the embodiments below. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0012] Comparative Example 1 Rice bran passed through a 20-mesh sieve was mixed with 0.1 M NaHCO3 solution at a ratio of 1:7 (w / w), incubated at 50 °C for 3 h, and then the slurry was filtered. The filtrate was centrifuged (10,000 rpm, 20 min, 4 °C), the cream layer was collected, washed with water, and centrifuged again to obtain rice bran oil bodies. The rice bran oil bodies were diluted 1-fold with phosphate buffer (0.01 M, pH 7.0) and the pH was adjusted to 7.0. The mixture was stirred in a closed container at 25 °C for 1 h to obtain a rice bran oil body emulsion.
[0013] Comparative Example 2 (1) Preparation of rice bran oil emulsion Rice bran passed through a 20-mesh sieve was mixed with 0.1 M NaHCO3 solution at a ratio of 1:7 (w / w), incubated at 50 °C for 3 h, and then the slurry was filtered. The filtrate was centrifuged (10,000 rpm, 20 min, 4 °C), the cream layer was collected, washed with water, and centrifuged again to obtain rice bran oil bodies. The contents of lipids and proteins in rice bran oil bodies were determined, and rice bran oil emulsions stabilized by rice bran proteins with equal contents were prepared according to the contents of lipids and proteins in the oil bodies.
[0014] (2) Construction of rice bran oil emulsion with tannic acid interfacial self-assembly Tannic acid powder was dispersed in phosphate buffer (0.01 M, pH 7.0) at a concentration of 0.2 mg / mL. Tannic acid solution and rice bran oil emulsion were mixed in equal proportions, the pH of the mixture was adjusted to 7.0, and the mixture was stirred in a closed container at 25 °C for 1 h, and then dialyzed (molecular weight cutoff 3.5 kDa) at 4 °C for 24 h (deionized water was replaced 10 times) to remove unreacted tannic acid, and finally an emulsion was obtained.
[0015] Comparative Example 3 (1) Preparation of rice bran oil emulsion Rice bran passed through a 20-mesh sieve was mixed with 0.1 M NaHCO3 solution at a ratio of 1:7 (w / w), incubated at 50 °C for 3 h, and then the slurry was filtered. The filtrate was centrifuged (10,000 rpm, 20 min, 4 °C), the cream layer was collected, washed with water, and centrifuged again to obtain rice bran oil bodies. The contents of lipids and proteins in rice bran oil bodies were determined, and rice bran oil emulsions stabilized by rice bran proteins with equal contents were prepared according to the contents of lipids and proteins in the oil bodies.
[0016] (2) Construction of rice bran oil emulsion with tannic acid interfacial self-assembly Tannic acid powder was dispersed in phosphate buffer (0.01 M, pH 7.0) at a concentration of 1 mg / mL. Tannic acid solution and rice bran oil emulsion were mixed in equal proportions, the pH of the mixture was adjusted to 7.0, and the mixture was stirred in a closed container at 25 °C for 1 h, and then dialyzed (molecular weight cutoff 3.5 kDa) at 4 °C for 24 h (deionized water was replaced 10 times) to remove unreacted tannic acid, and finally an emulsion was obtained.
[0017] Example 1 (1) Preparation of natural rice bran oil bodies Rice bran passed through a 20-mesh sieve was mixed with 0.1 M NaHCO3 solution in a ratio of 1:7 (w / w), incubated at 50 °C for 3 h, and then the slurry was filtered. The filtrate was centrifuged (10,000 rpm, 20 min, 4 °C), the cream layer was collected, washed with water, and centrifuged again to obtain rice bran oil bodies.
[0018] (2) Construction of rice bran oil emulsion with tannic acid interfacial self-assembly Tannic acid powder was dispersed in phosphate buffer (0.01 M, pH 7.0) at a concentration of 0.2 mg / mL. Tannic acid solution and rice bran oil bodies were mixed in equal proportions, the pH of the mixture was adjusted to 7.0, and the mixture was stirred in a closed container at 25 °C for 1 h, and then dialyzed (molecular weight cutoff 3.5 kDa) at 4 °C for 24 h (deionized water was replaced 10 times) to remove unreacted tannic acid, and finally a rice bran oil body emulsion with tannic acid interfacial self-assembly was obtained.
[0019] Example 2 (1) Preparation of natural rice bran oil bodies Rice bran passed through a 20-mesh sieve was mixed with 0.1 M NaHCO3 solution in a ratio of 1:7 (w / w), incubated at 50 °C for 3 h, and then the slurry was filtered. The filtrate was centrifuged (10,000 rpm, 20 min, 4 °C), the cream layer was collected, washed with water, and centrifuged again to obtain rice bran oil bodies.
[0020] (2) Construction of rice bran oil emulsion with tannic acid interfacial self-assembly Tannic acid powder was dispersed in phosphate buffer (0.01 M, pH 7.0) at a concentration of 1 mg / mL. Tannic acid solution and rice bran oil bodies were mixed in equal proportions, the pH of the mixture was adjusted to 7.0, and the mixture was stirred in a closed container at 25 °C for 1 h, and then dialyzed (molecular weight cutoff 3.5 kDa) at 4 °C for 24 h (deionized water was replaced 10 times) to remove unreacted tannic acid, and finally a rice bran oil body emulsion with tannic acid interfacial self-assembly was obtained.
[0021] 1. Tannic acid binding capacity detection The Folin-Ciocalteu method was used to determine the binding amount of tannic acid in the emulsion of tannic acid interfacial self-assembly bound to rice bran oil bodies. The dialyzed emulsion was dissolved in deionized water (1 mg / mL), and the sample (1 mL) was mixed with Folin-Ciocalteu solution (1 mL, 1 M), reacted at 25 °C in the dark for 5 min, and sodium carbonate aqueous solution (4 mL, 7.5%, w / v) was added, and the reaction continued at 25 °C in the dark for 2 h. The absorbance at 760 nm was measured by UV-visible spectrophotometer, and deionized water was used as a blank control. The content of tannic acid in the dialyzed emulsion was determined according to the standard curve. The tannic acid binding amount was calculated as follows: Table 1: Zeta potential and average particle size of rice bran oil emulsions in Comparative Example 1, Example 1 and Example 2 2. Zeta potential and average particle size detection The rice bran oil emulsion sample was diluted with phosphate buffer (1 mM) of corresponding pH value to an oil content of about 0.006%. The zeta potential and average particle size of the droplets were measured using a nano-laser particle size analyzer. The refractive indices of the dispersed phase and the continuous phase were set to 1.45 and 1.33, respectively, and the equilibrium time was 120 s. The measurement was repeated three times at 25 °C.
[0022] 3. Microstructure Observation Laser confocal microscopy test The rice bran oil bodies were diluted 5 times with phosphate buffer (1 mM, pH 6.1), and then the samples were stained with Nile red (1 mg / mL dissolved in dimethyl sulfoxide, excitation wavelength: 488 nm) to stain core lipids (1:50, v / v) and Fast Green FCF (1 mg / mL dissolved in ultrapure water, excitation wavelength: 640 nm) to stain proteins (3:50, v / v), and then observed under a 60× objective lens (oil immersion) using a 10× eyepiece.
[0023] For transmission electron microscopy test, 10 μL of sample was dropped on the copper grid for 1 min, and the floating liquid was removed by filter paper. Then 10 μL of uranyl acetate was dropped on the copper grid for 1 min, and the floating liquid was removed by filter paper. The sample was dried at room temperature for several minutes, and then imaged at 100 kV.
[0024] 4. Lipid oxidation and protein oxidation detection during storage Rice bran oil emulsion samples were spontaneously oxidized at 25 ℃ in the dark. The lipid oxidation of the emulsion was evaluated by monitoring the formation of primary oxidation products (hydroperoxides), and the protein oxidation was evaluated by measuring the changes in the carbonyl and free thiol contents.
[0025] (1) Hydroperoxide concentration The sample (0.3 mL) was mixed with isooctane / isopropanol (1.5 mL, 3:1, v / v), shaken three times (10 s each time), centrifuged at 3,400 g for 2 min, and the supernatant (0.2 mL) was mixed with methanol / n-butanol (2.8 mL, 2:1, v / v) and thiocyanate / Fe 2+ The solution (30 μL) was mixed with an equal volume of 3.94 M thiocyanate solution and Fe 2+ Thiocyanate / Fe was prepared by mixing solutions (equal volumes of 0.144 M FeSO4 and 0.132 M BaCl2 (containing 0.4 M HCl) and centrifuging to obtain the supernatant). 2+ The resulting solution was allowed to stand at room temperature for 19 min, and the absorbance at 510 nm was measured using a UV-visible spectrophotometer. The hydroperoxide concentration (mmol / L) was determined based on the cumene hydroperoxide calibration curve.
[0026] (2) Protein carbonyl content The changes in protein carbonyl content during the oxidation of rice bran oil body emulsions were determined by 2,4-dinitrophenylhydrazine (DNPH) colorimetric method. 0.8 mL of emulsion sample was mixed with 0.6 mL of DNPH solution (10 mM, dissolved in 2 M HCl) and incubated at 37 °C for 60 min, vortexing for 5 s every 10 min. Then 0.75 mL of trichloroacetic acid (20%, v / v) was added to the reacted sample, and the protein was precipitated by centrifugation at 12,000 rpm for 15 min. The precipitated pellet was washed three times with 1.5 mL of ethanol-ethyl acetate (1:1, v / v), redissolved in 1 mL of guanidine solution (6 M), and incubated at 37 °C for 15 min. Finally, the absorbance at 370 nm was recorded to quantify the carbonyl concentration. The concentration of soluble protein in the guanidine solution was determined by the Bradford method, and the protein carbonyl content was expressed as μmol / g soluble protein with a molar extinction coefficient of 22,000 M. -1 cm -1.
[0027] (3) Free thiol content The sample was diluted 20 times with PBS (10 mM, pH 7), and then 0.5 mL of the diluted sample was mixed with 5 mL of Tris-Gly-urea buffer (pH 8, 10.4 g Tris, 6.9 g Gly, 1.2 g EDTA, 480 g urea dissolved in deionized water, and the volume was fixed to 1000 mL). The resulting mixture was stirred at room temperature for 30 min and then centrifuged at 12,000 rpm for 10 min. 2 mL of the supernatant was reacted with 0.04 mL of Ellman's reagent, in which 5,5'-dithio-bis(2-nitrobenzoic acid) (DNTB, 4 mg / mL) was dissolved in Tris-Gly buffer (pH 8, 10.4 g Tris, 6.9 g Gly, 1.2 g EDTA dissolved in deionized water, and the volume was fixed to 1000 mL) to prepare fresh Ellman's reagent. The free thiol content was quantified by recording the absorbance at 412 nm, with PBS (10 mM, pH 7) as a blank. The results were expressed as μmol / g soluble protein with a molar extinction coefficient of 13,600 M -1 cm -1 .
[0028] 5. Detection of the interaction between tannic acid and rice bran oil body interface components (1) Raman spectroscopy detection The Raman spectra of the samples were recorded in situ on a confocal Raman microscope. First, the light was focused directly on the sample, and a 5× objective was selected to obtain a white light microscope image of the sample. The experimental power was 100 mW, the wavelength was 785 nm, the laser acquisition time was 20 s, and the scanning range was 400-4000 cm. -1 The Raman spectrum of rice bran oil emulsion was obtained in the above region.
[0029] (2) Infrared spectrum detection The freeze-dried rice bran oil emulsion sample was mixed with 100 mg KBr powder, ground into fine powder and pressed into tablets. The FTIR spectra were analyzed at 400-4000 cm -1 The infrared spectrum was obtained after scanning 32 times in the wavenumber range with a resolution of 4 cm -1 .
[0030] (3) Circular dichroism detection The interfacial protein powder was dissolved to 1 mg / mL in phosphate buffer (1 mM, pH 7.4), and the changes in the secondary structure were determined using a circular dichroism spectrometer. The sample was placed in a quartz cuvette with a path length of 1 mm, and the spectrum was scanned at 190-260 nm under a continuous N2 flow at room temperature. The working parameters were set to 0.5 s per point, 1 nm step size, and 1 nm bandwidth, and then the CDNN 2.1 software was used to estimate the content of α-helix, β-fold, β-turn, and random coil in the secondary structure of the interfacial protein.
[0031] As shown in Table 1, tannic acid binds to the interface of rice bran oil bodies, and the amount of bound tannic acid increases in a dose-dependent manner with the increase of its concentration. All emulsion samples exhibited a strong negative surface potential, which is due to the high negative charge of the rice bran oil bodies themselves and the fact that tannic acid acts on the interfacial oil body proteins, which may expand the protein structure and reduce the exposure of positively charged groups, thereby increasing the negative charge on the surface of the emulsion. The particle size of the tannic acid-bound rice bran oil body emulsion gradually decreases, indicating that the electrostatic repulsion between the emulsion droplets caused by tannic acid is stronger than the interaction forces (hydrophobic interactions and hydrogen bonds) that cause the system to aggregate.
[0032] like Figure 1 As shown, the laser confocal microscope image shows that the rice bran oil body presents a uniform spherical droplet structure before and after the self-assembly combination at the tannic acid interface. With the increase of tannic acid concentration, the dispersibility of the emulsion droplets increases and the average particle size decreases, which is consistent with the results of the test in Table 1. Through transmission electron microscopy, it was found that there was adsorption of submicron-level interface proteins and small-sized oil bodies on the interface of the rice bran oil body emulsion droplets without the addition of polyphenols. At the same time, there was a certain proportion of loosely adhered protein aggregates at the interface of the comparative rice bran oil body. The fibrous regional structure was observed in Example 2, which may be because tannic acid promoted the interaction between adjacent oil droplets, produced an ordered fibrous regional structure around the oil droplets, and formed a denser accumulation at the interface of the oil body emulsion.
[0033] Figure 3 The results showed that the concentration of hydroperoxide in rice bran oil emulsion increased with the storage time (0-96 h), indicating the oxidation and degradation of lipids. Under the influence of oxidation, the emulsion has stratified in appearance ( Figure 2 ). The self-assembly of tannic acid at the interface of rice bran oil bodies effectively reduced the accumulation of lipid oxidation products in the oil body emulsion, and as the concentration of tannic acid increased, the inhibition of oxidation became more obvious.
[0034] The increase of carbonyl groups and the loss of sulfhydryl groups are the two most significant changes in oxidized proteins. Figure 4It can be seen that with the increase of storage time, the protein carbonyl content in the rice bran oil emulsion sample increased significantly, and there was an obvious positive correlation between the carbonyl content of the primary oxidation products of lipids and the carbonyl content of the protein oxidation products, indicating that lipid oxidation affects protein oxidation to a certain extent. Figure 5 As shown, it can be seen that compared with pure rice bran oil bodies, the tannic acid interface self-assembly binding can significantly reduce the loss of thiol groups in rice bran oil bodies during storage and inhibit interface protein oxidation. It is calculated that compared with the comparative example, the formation of lipid primary oxidation products in Example 2 is inhibited by 20.3%, and the increase of carbonyl groups and the loss of thiol groups are inhibited by 15.6% and 12.09%, respectively.
[0035] like Figure 6 As shown, at 2855 cm -1 , 2900 cm -1 and 2934 cm -1 The characteristic Raman peaks observed at 2855 cm-1 are the symmetric and asymmetric C−H stretching vibrations of CH2 and CH3 in fat molecules, among which the CH2 symmetric stretching band appears at 2855 cm-1. -1 The CH2 asymmetric stretching band appears at 2900 cm -1 , CH3 symmetric stretching band near 2934 cm -1 I 2855 / I 2900 and I 2934 / I 2900 The intensity ratio of I provides useful information for evaluating lipid packing effects and indicates the ordered or disordered state of acyl chains in different lipid phases, especially 2855 / I 2900 The disorder or order of the acyl chains due to lateral interchain interactions was directly monitored. The lower intensity ratio (I 2855 / I 2900 ) reflects the increase of interchain vibration coupling and the decrease of acyl chain mobility. 2855 / I 2900 The values gradually decreased, confirming the decrease in the mobility of lipid acyl chains, indicating that after the self-assembly of tannic acid with interfacial phospholipids and oil body proteins, the interaction between the interfacial components and the core lipids was stronger, which was beneficial to the stability of rice bran oil bodies.
[0036] Figure 7 Display wave number is 4000~3100 cm -1 The characteristic peak at 1652 cm-1 shifted and its intensity gradually increased, which was due to the formation of hydrogen bonds between the multiple phenolic hydroxyl groups in the chemical structure of tannic acid and the interfacial phospholipids and oil body proteins. -1) red-shifted to 1650 cm in the case of tannic acid self-assembly. -1 and 1644 cm -1 , confirming the existence of hydrophobic interactions between tannic acid and interfacial components.
[0037] Figure 8 As shown in the figure, under the self-assembly combination of tannic acid interface, the α-helix content of oleosomal protein decreased from the initial 19.30% to 15.99%, the β-turn content also decreased, while the β-fold and random coil structures increased from 38.44% and 25.17% to 39.73% and 29.67%, respectively. In the secondary structure of proteins, α-helix is a tight spiral structure stabilized by intrachain hydrogen bonds formed by carbonyl oxygen (C=O) and amino hydrogen (N-H) groups. The decrease in the relative content of α-helix in oleosomal protein indicates that the stable and orderly structure of the protein has been destroyed, while the increase in the relative content of random coil further indicates that the structure of oleosomal protein becomes looser and more disordered after hydrogen bonding or hydrophobic interaction with tannic acid, thus forming a denser stacking at the oil body interface, limiting the diffusion of pro-oxidants.
[0038] Depend on Fig. 9 It can be seen that although the rice bran oil emulsion stabilized by rice bran protein in Comparative Examples 2 and 3 is reduced in size after being combined with tannic acid, due to the lack of a phospholipid layer on the interface, only the interaction between tannic acid and rice bran protein makes the droplet size reduction degree smaller than that in Example 1 and Implementation 2, so the electrostatic repulsion and steric hindrance between droplets are weaker, and the density of the rice bran oil emulsion interface is worse than that in Comparative Example 1. In Example 1 and Implementation 2, the droplet size is reduced after self-assembly of tannic acid and the interfacial phospholipids and oil body proteins of rice bran oil bodies through hydrogen bonds and hydrophobic interactions, the electrostatic repulsion and steric hindrance between droplets are enhanced, and the interface layer is denser, thereby limiting the diffusion of pro-oxidants and improving the oxidative stability of the oil bodies.
[0039] In summary, under mild conditions, the technology of the present invention uses tannic acid and the interfacial phospholipids and oil body proteins of plant oil bodies to self-assemble through hydrogen bonds and hydrophobic interactions. The plant oil bodies can still maintain the natural water-in-oil structure of the core lipids coated by the phospholipid-oleosin membrane, but the droplet size is reduced, the electrostatic repulsion and steric hindrance between the droplets are enhanced, the interface layer is denser, and the diffusion of pro-oxidants is limited. Therefore, the oxidation of core lipids and proteins in plant oil bodies can be effectively inhibited, the oxidation of core lipids can be inhibited by more than 20%, and the oxidation of proteins can be inhibited by more than 12%, which significantly improves the oxidative stability of plant oil bodies, thereby promoting the industrial application of natural plant oil bodies in food, cosmetics, and pharmaceutical systems.
[0040] The above description is only a preferred embodiment of the present invention. It should be noted that, without departing from the spirit and essence of the present invention, those skilled in the art may make various modifications, combinations, changes or substitutions to the details and features of the present invention. These modifications, combinations, changes or substitutions should also be understood to be included in the scope of protection claimed by the present invention.
Claims
1. A method for improving the oxidative stability of vegetable oil bodies by interfacial self-assembly of tannic acid, characterized in that: The following steps are involved: (1) Preparation of natural plant oil bodies; (2) Construction of tannic acid interfacial self-assembled plant oil body emulsion: Tannic acid solution was mixed with plant oil bodies, and the pH of the mixture was adjusted to 7.
0. The hydrogen bonds and hydrophobic interactions between tannic acid and the interfacial phospholipids and oil body proteins of the plant oil bodies were regulated to obtain tannic acid interfacial self-assembled plant oil body emulsion.
2. The method for improving the oxidative stability of vegetable oil bodies by interfacial self-assembly of tannic acid according to claim 1, characterized in that: Mix crushed soybeans, peanuts, flax seeds, almonds, walnuts or rice bran with NaHCO3 solution in proportion, incubate for a certain period of time, filter the slurry, centrifuge the filtrate, collect the cream layer, wash with water and centrifuge again to obtain plant oil bodies.
3. The method for improving the oxidative stability of vegetable oil bodies by interfacial self-assembly of tannic acid according to claim 1, characterized in that: Tannic acid powder was dispersed in phosphate buffer at a concentration of 0.2-1 mg / mL.
4. The method for improving the oxidative stability of vegetable oil bodies by interfacial self-assembly of tannic acid according to claim 1, characterized in that: The mass ratio of tannic acid solution to vegetable oil is 1:0.2~1.
Citation Information
Patent Citations
Chitin and tannic acid composite colloidal particle emulsifier as well as preparation method and application thereof
CN112106975A
Lycium seed oil Pickering emulsion gel as well as preparation method and application thereof
CN118085330A
Zein-based oleogel based on polyphenol self-assembled coating as well as preparation method and application of zein-based oleogel
CN118235801A
Protein-polyphenol composite nanoparticle, preparation method and application of protein-polyphenol composite nanoparticle in antioxidant Pickering emulsion
CN118633675A